The Bible’s Narrative Rhythm, Exegesis’s Enlightenment—A Review of The History and Methodology of Biblical Interpretation - SU , Jiayi (Journal of Research for Christianity in China (JRCC), 2024)
Tian Haihua, The History and Methodology of Biblical Interpretation. Beijing: Social Sciences Academic Press, 2024. 451,000 characters. Price: ¥136.